Ageism in healthcare technology: the older patients' aspirations for improved online accessibility. Issue 3 (13th July 2022) - Zoorob, Dani; Hasbini, Yasmin; Chen, Katherine; Wangia-Anderson, Victoria; Moussa, Hind; Miller, Brian; Brobst, Debi
Abstract: Objective: To identify concerns, barriers and facilitators impacting the use of patient portals by older patients as well as desired features in future updates. Materials and Methods: This is a cross-sectional study consisting of 2 focus group discussions culminating in an anonymous survey administered to women who were 65 years and older receiving urogynecologic care in Northwest Ohio. Results: Of the 205 women surveyed (91% response rate), providers and healthcare systems play the primary 2 roles (73% and 69%, respectively) in facilitating patients' use of patient portal systems and telehealth applications. Barriers to use revolved around technical difficulties (50%), privacy concerns (45%), and cost of technology (24%). The most important features desired were the ability to modify the text size within the application (47%) and an intuitive, simple interface (46%). Additional assistance for navigating technical challenges was suggested, specifically set-up of accounts (36%), saving and sharing information with caregivers (35%), and sign-in and navigation of portals (32%). Conclusion: The paucity of age-aligned medical access software and products may lead to worsening of digital exclusion and disparities in healthcare. Portal application developers and healthcare systems must advance efforts that consider the needs of those who may be older when designing patient portals. Lay Summary: Older patients disproportionally underutilize patient portals and electronic medical systems placing them at a healthcare disadvantage. This study sought to identify the concerns, barriers, and facilitators that impact their use of such portals, as well as design and feature enhancements which may augment their uptake. This was established using focus group discussions and anonymous surveys. Our results suggested that providers and healthcare systems, per se, can play a significant role in motivating patients to use electronic medical records. Concerns of the older patients revolved around privacy, cost, and technical concerns. The latter primarily targeted sign-on difficulties, intuitiveness/struggles with navigation within the portal, and inability to easily share information with caregivers. Modifications requested included developing support options for personal limitations (such as arthritis, reduced visual acuity, and other medical conditions hindering ease of use). Additional features requested included the ability to modify the size of text and icons, more pictures, drop-down menus, and voice commands.